2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin (TCDD)-induced suppression of immunity in THP-1-derived macrophages and the possible mechanisms. (15th October 2021) - Li, Xinyan; Li, Na; Han, Yingnan; Rao, Kaifeng; Ji, Xiaoya; Ma, Mei
Abstract: 2, 3, 7, 8-Tetrachlorodibenzo-p-dioxin (TCDD) is a well-known immunotoxic environmental pollutant. However, most immunotoxicology studies of TCDD were based on the animal models and the inner mechanisms have just focused on a few genes/proteins. In this study, the immune functions of THP-1-derived macrophages was measured with in-vitro bioassays after 24-h exposure of TCDD including environmentally relevant concentrations. RNA-seq and Weighted Gene Co-expression Network Analysis were used to characterize the immunotoxicity molecular mechanisms. Our study is the first report on the TCDD-induced effects of cell adhesion, morphology, and multiple cytokines/chemokines production on THP-1 macrophages. After TCDD treatment, we observed an inhibited cell adherence, probably attributed to the suppressed mRNA levels of adhesion molecules ICAM-1, VCAM-1 and CD11b, and a decrease in cell pseudopodia and expression of F-actin. The inflammatory cytokines TNF-α, IL-10 and other 8 cytokines/chemokines regulating granulocytes/T cells and angiogenesis were disrupted by TCDD. Alternative splicing event was found to be a sensitive target for TCDD. Using WGCNA, we identified 10 hub genes (TNF, SRC, FGF2, PTGS2, CDH2, GNG11, BDNF, WNT5A, CXCR5 and RUNX2) highly relevant to these observed phenotypes, suggesting AhR less important in the effects TCDD have on THP-1 macrophages than in other cells. Our findings broaden the understanding of TCDD immunotoxicity on macrophages and provide new potential targets for clarifying the molecular mechanisms. Graphical abstract: Image 1 Highlights: Environmentally relevant dose of TCDD suppressed the immunity of THP-1 macrophages. TCDD inhibit the cell adhesion and morphology of THP-1 macrophages. TCDD altered the production of 10 cytokines/chemokines in THP-1 macrophages. Low dose of TCDD (1 nM) can significantly reduce the alternative splicing events. AhR is not a crucial target in macrophages when attacked by TCDD as in other cells.